Resveratrol Reduces COMPopathy in Mice Through Activation of Autophagy - Jacqueline T Hecht (JBMR Plus, 2021)
ABSTRACT Misfolding mutations in cartilage oligomeric matrix protein (COMP) cause it to be retained within the endoplasmic reticulum (ER) of chondrocytes, stimulating a multitude of damaging cellular responses including ER stress, inflammation, and oxidative stress, which ultimately culminates in the death of growth plate chondrocytes and pseudoachondroplasia (PSACH). Previously, we demonstrated that an antioxidant, resveratrol, substantially reduces the intracellular accumulation of mutant‐COMP, dampens cellular stress, and lowers the level of growth plate chondrocyte death. In addition, we showed that resveratrol reduces mammalian target of rapamycin complex 1 (mTORC1) signaling, suggesting a potential mechanism. In this work, we investigate the role of autophagy in treatment of COMPopathies. In cultured chondrocytes expressing wild‐type COMP or mutant‐COMP, resveratrol significantly increased the number of Microtubule‐associated protein 1A/1B‐light chain 3 (LC3) vesicles, directly demonstrating that resveratrol‐stimulated autophagy is an important component of the resveratrol‐driven mechanism responsible for the degradation of mutant‐COMP. Moreover, pharmacological inhibitors of autophagy suppressed degradation of mutant‐COMP in our established mouse model of PSACH. In contrast, blockage of the proteasome did not substantially alter resveratrol clearance of mutant‐COMP from growth plate chondrocytes. Mechanistically, resveratrol increased SIRT1 and PP2A expression and reduced MID1 expression and activation of phosphorylated protein kinase B (pAKT) and mTORC1 signaling in growth plate chondrocytes, allowing clearance of mutant‐COMP by autophagy. Importantly, we show that optimal reduction in growth plate pathology, including decreased mutant‐COMP retention, decreased mTORC1 signaling, and restoration of chondrocyte proliferation was attained when treatment was initiated between birth to 1 week of age in MT‐COMP mice, translating to birth to approximately 2 years of age in children with PSACH. These results clearly demonstrate that resveratrol stimulates clearance of mutant‐COMP by an autophagy‐centric mechanism. © 2020 The Authors. JBMR Plus published by Wiley Periodicals LLC. on behalf of American Society for Bone and Mineral Research.